Assessment of Working Length of Root Canal in Mandibular First Primary Molar in Children Aged between 2 to 6 Years - Meghana Reddy J1 , Deepa Gurunathan2 , Deepika Rajendran3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
In the endodontic glossary the working length is defined as the distance from a coronal reference point tothe point at which canal preparation and obturation should terminate. Pulpectomy is a process of completeremoval of the necrotic pulp from the root canals of primary teeth and filling them with an inert resolvablematerial so as to maintain the tooth in the dental arch. A University based study was conducted on mandibularprimary first molar. Various pathologies such as pain, swelling, abscess and resorption were considered.Data collection was done by reviewing the patient records and analysing the data of 501 patients from June2019 to March 2020, then excel tabulation, Statistical analysis was done using SPSS and Pearson chi-squaretest was performed. The total number of patients seen were 501, age ranged from 2 to 6 years. Out of thetotal population 42.91% (215) were female and 57.09% (286) were males. The mean length of mesio buccalcanal was 10.76 mm, mesio distal canal – 10.88 mm, and the distal canal was 11.2 mm in the mandibularfirst primary molar. Pulpal pathology with mean working length of the root canals were as follows, In painthe mesio buccal root had 10.76 mm, mesio lingual root had 10.81 mm and the distal root had 12.01 mm.Abscess the mesio buccal root had 10.75 mm, mesio lingual root 10.79 mm and the distal root 12.03 mm.Swelling the mesio buccal root had 10.75 mm, mesio lingual root had 10.80 mm, and the distal root had12mm, Resorption mesio buccal root had 10.77 mm, mesio lingual root had 10.78 mm, and the distal root had11.8 mm. In regard to various pathogens such as pain,swelling, abscess and resorption the working lengthwas determined as 10.76 mm for mesio buccal root, 10.88 mm for mesio lingual root and 11.2 mm for distalroot of the mandibular first primary molar.